2012
DOI: 10.1017/s0954102012000193
|View full text |Cite
|
Sign up to set email alerts
|

Determination of geomorphological and volumetric variations in the 1970 land volcanic craters area (Deception Island, Antarctica) from 1968 using historical and current maps, remote sensing and GNSS

Abstract: During the nearly 40 years covered by the study, major height differences of over ± 25 m have been revealed in the volcanic landscape of the 1970 craters in Deception Island, an active volcano in the South Shetland Islands (West Antarctica). In the last 14 years, the mean volcanic filling rate has been 1 m yr -1 and the mean erosion rate has been -0.2 m yr -1 . There has been considerable landform modification mainly associated with landslide-induced accumulation, and erosion may indicate the craters' fill ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…From the 2007–08 until the 2012–13 campaign, the geodetic networks were updated and extended, weather and tidal data were obtained for the determination of the mean sea level, the geodesic reference framework was updated and new cartography obtained (Torrecillas et al . 2011, Berrocoso et al 2012, Vidal et al 2012, Jigena et al 2014).…”
Section: Equipment Data Acquisition and Data Processingmentioning
confidence: 98%
See 1 more Smart Citation
“…From the 2007–08 until the 2012–13 campaign, the geodetic networks were updated and extended, weather and tidal data were obtained for the determination of the mean sea level, the geodesic reference framework was updated and new cartography obtained (Torrecillas et al . 2011, Berrocoso et al 2012, Vidal et al 2012, Jigena et al 2014).…”
Section: Equipment Data Acquisition and Data Processingmentioning
confidence: 98%
“…The first experimental geoid for Deception Island, included in the Multidisciplinary Scientific Information Support System (SIMAC) for Deception Island (Torrecillas et al 2006, Berrocoso et al 2008), was calculated according to this elevation reference for the BARG geodetic benchmark (Fig. 3), providing a mean N value of -19.59 m in that area in 2008 (Berrocoso et al 2008, 2012). This value differed from the 1992 value by 6.59 m.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…These thresholds can be used to determine the temporal probability of the occurrence of landslides as a part of a landslide early warning system (LEWS). The thresholds can be estimated using empirical methods [9][10][11][12], probabilistic methods [8,13,14], and/or physical methods [15,16], and we can use other tools like geographic information system (GIS) [17] and global positioning system (GPS) [18,19] and new technologies in order to make the calculation processes automatic [20,21]. When long-term monitoring data is not available for the study area, it is often difficult to identify the triggering rainfall corresponding to landslides [22].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of volumetric erosion models developed for other oceanic islands (Garvin et al, 2000; Berrocoso et al, 2012; Ramalho et al, 2013; Perron, 2017), quantify the observed island erosion to investigate geologic processes that stabilize such fragile landscape systems, such as hydrothermal alteration (e.g., Jakobsson, 1978)…”
Section: Introductionmentioning
confidence: 99%
“…We hoped to evaluate whether island volumetric changes due to natural causes at meter scales (NRC ES Decadal Survey, ) could be effectively measured. Preliminary results (Figure ) suggested the following approach: Using meter‐resolution satellite observations, document the volumetric rates of change of the overall island for the purpose of accurately projecting island survival timelines On the basis of volumetric erosion models developed for other oceanic islands (Garvin et al, ; Berrocoso et al, ; Ramalho et al, ; Perron, ), quantify the observed island erosion to investigate geologic processes that stabilize such fragile landscape systems, such as hydrothermal alteration (e.g., Jakobsson, ) …”
Section: Introductionmentioning
confidence: 99%